Training, Working Motivation and Performance of Non-Permanent Workers-Auxiliary Staff of Agricultural Extension Workers (THL-TBPP) - Rinofi; Asmawi; Zul Irfan (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2020)
This study aimed to analyze the effect of training and working motivation on performance of the non-permanent workers-auxiliary staff of agricultural extension workers (THL-TBPP) in West Sumatra. The research method used was a survey approach with quantitative methods and the techniques of data analysis used were descriptive and inductive analysis. The research results indicate that the extension management training of THL-TBPP on training material, facilitators, and training organizing aspects have been conducted very well. The extension workers’ motivation of THL-TBPP regarding the needs of achievement and affiliation was very high, whilst the motivation over the authority was medium-worth. The performance of THL-BPP extension workers from the counselling preparation, implementation, counselling to the evaluation and reporting was very high in which the extension workers of THL-BPP carried out all the duty very well. The training had a significant level of 0.000 < 0.05 so that it fulfilled the condition to be the supporting variable of extension workers performance. It means that if the performance of THL-TBPP extension workers in West Sumatera increases, then it is caused by one of the training done. The agricultural extension management training has given a positive impact on the improvement of THL-TBPP extension workers performance in West Sumatera. The motivation had a significance level of 0.004 < 0.05 so that it has fulfilled the condition to be the supporting variable of extension workers performance as well. The high motivation for extension workers will increase the performance of THL-TBPP extension workers in West Sumatera.